2007
DOI: 10.1007/s00540-007-0544-8
|View full text |Cite
|
Sign up to set email alerts
|

General anesthesia and methylenetetrahydrofolate reductase deficiency

Abstract: Methylenetetrahydrofolate reductase (MTHFR) deficiency is an autosomal recessive disorder with a spectrum of manifestations including neurological symptoms, premature arteriosclerosis, and venous and arterial thrombosis. Most patients are heterozygous for multiple MTHFR substitutions; small minorities are homozygous for mutations at this locus. Among these mutations, the C677T polymorphism is the most deleterious. Nitrous oxide use in anesthesia leads to significant increases in plasma homocysteine. We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…Despite these measures, she had a coronary ischaemic insult and renal artery thrombosis in the postoperative period. The authors concluded that such patients should be closely followed postoperatively for the occurrence of myocardial infarction and pulmonary emboli even though N 2 O was not used in anaesthesia management (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these measures, she had a coronary ischaemic insult and renal artery thrombosis in the postoperative period. The authors concluded that such patients should be closely followed postoperatively for the occurrence of myocardial infarction and pulmonary emboli even though N 2 O was not used in anaesthesia management (2).…”
Section: Discussionmentioning
confidence: 99%
“…Manifestations of the disease are neurological symptoms (progressive hypotonia, convulsions and physicomotor retardation), premature atherosclerosis and venous and arterial thrombosis. Hyperhomocysteinemia predisposes patients to venous and arterial thrombosis with a three to six-fold increased risk compared to the normal population (1,2).…”
mentioning
confidence: 99%
“…8,9 In patients with MTHFR, nitrous oxide should not be used because it inhibits methionine synthetase, resulting in reduction of the conversion of homocysteine to methionine, thus increasing systemic homocysteine levels. 10 Optimal perioperative management of patients with PNH includes the use of red blood cell transfusion, avoidance of hypoxaemia, acidosis, dehydration, drugs known to activate complement reaction and antibiotic prophylaxis. 7 A major component of anaesthetic management was to avoid or at least minimise complement activation.…”
Section: Editormentioning
confidence: 99%
“…According to our literature research anesthesia management of the disorder is rarely reported among adults compared to pediatric cases To our knowledge, this is the first cardiac surgical case report in the literature. We found three adult case reports: one for elective colon surgery, the second for cesarean section, and the last one for urgent toe amputation (3)(4)(5). All three cases experienced occlusive events prior to surgery that led to the diagnosis of MTHFR deficiency.…”
mentioning
confidence: 99%